ANALISIS KONSEP PERASAAN DAN EMOSI DALAM PERSPEKTIF PSIKOLOGI PENDIDIKAN ISLAM - Muthrofin, Khoirul; Hakim, Luqman (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2025)
This article is based on phenomena in the field of education, which indicate that most educators and parents tend to overlook the psychological aspects of children’s learning. In reality, education should not only focus on intellectual and physical intelligence but must also develop the psychological aspects of students to maximize the learning process. This study aims to analyze and explore the concept of feelings and emotions in psychology, the concept of feelings and emotions from the perspective of Islamic education, and their relevance to Islamic education learning. This research employs a qualitative descriptive method with a literature study approach. The findings of the study conclude several key points. First, feelings and emotions are psychological elements that play a crucial role in students’ cognitive development and enable them to socialize in real life. Second, the psychological concept of feelings and emotions aligns with the concept of al-Nafs in Islamic educational psychology, which refers to psychological phenomena as part of the inner spiritual component of human beings. Third, the concept of feelings and emotions is relevant to the learning process in Islamic education, which seeks to develop these two components to shape a well-rounded Muslim generation. Ultimately, educators must place greater emphasis on these psychological components and develop them positively through a comprehensive learning and guidance process to achieve the success of Islamic education goals.